PENERAPAN MEDIA TEKA-TEKI SILANG TERHADAP HASIL BELAJAR PPKN SISWA KELAS III SDS MUHAMMADIYAH SURO - Juliana, Rara; Sofiarini, Andriana; ., Aswarliansyah (LP4MK STKIP PGRI Lubuklinggau, 2024)
This research aims to determine the learning outcomes of PPKn class III students at SDS Muhammadiyah Suro after the application of crossword puzzle media has been significantly completed. The research method used is pre-experimental design. The population taken was all class III students at SDS Muhammadiyah Suro and the sample was class III students, totaling 25 students. The data collection technique uses a test in the form of essay questions. The data obtained were analyzed using the z-test at a significance level of a= 0.05. The research results showed that Zcount = 1.72 > Ztabel = 1.65, which shows that Ho was rejected and Ha was accepted with an average student learning outcome value of 74.28. So it can be concluded that student learning outcomes after implementing crossword media in PPKn learning for class III students at SDS Muhammadiyah Suro are significantly complete. Keywords: Hasil Belajar, Media Teka-Teki Silang